Two Bonebridge bone conduction hearing implant generations: audiological benefit and quality of hearing in children - Šikolová, Soňa; Urík, Milan; Hošnová, Dagmar; Kruntorád, Vít; Bartoš, Michal; Motyka, Oldřich; Jabandžiev, Petr (European archives of oto-rhino-laryngology, 2022)
PURPOSE: The study aimed to evaluate audiological benefits, quality of hearing and safety of two Bonebridge generation: BCI601 and BCI602 (MED-EL, Innsbruck, Austria) in children. METHODS: Twelve children were implanted: five BCI601 and seven BCI602 comprising of ten conductive hearing loss, and two single sided deaf SSD subjects. Audiological outcomes tested were sound field audiometry, functional gain, speech recognition threshold (SRT50), speech recognition in noise (SPRINT) and localisation abilities. Subjective measures were Speech, Spatial and Qualities of Hearing Scale (SSQ12). RESULTS: The mean FG with the BCI601 was 25.0 dB and with the BCI602 28.0 dB. The benefit in SRT50 was 23.2 dB and 33.8 dB, respectively. The mean benefit in SPRINT was 15% and 6.7% and the localisation ability improved from 33.3° to 16° and from 26.2° to 17.6°, respectively. The two SSD subjects reported a FG of 17 dB, a benefit in SRT50 of 22.5 and a benefit in SPRINT of 20%. Subjective outcomes improved significantly and even exceeded the values of their age-and sex matched normal hearing peers. One revision was reported: a retroauricular emphysema above the implant occurred 12 months post-OP, it was resolved operatively with the implant still being functional. CONCLUSION: The pediatric cohort reports significant audiological benefit, even exceeding that of the age- and sex matched control. The combination of the high safety and audiological benefit makes the Bonebridge a comfortable and effective option in hearing rehabilitation in children.
Keywords: Child; sluch; sluchové testy; Hearing Aids; kostní vedení zvuku; Speech Perception; převodní nedoslýchavost; percepce řeči; Bone Conduction; Hearing Tests; výsledek terapie; sluchové pomůcky; Hearing Loss, Conductive; Humans; lidé; Treatment Outcome; dítě; Hearing